Les études consacrées à l’histoire de la diaspora chinoise menées en République populaire de Chine depuis 1979, essai de synthèse - Xavier Paulès (Diasporas: Circulations, Migrations, Histoire)
The historiography of the diaspora in the People’s Republic of China is altogether characterized by a strong subordination to the government’s political agenda. From 1980 to 2010, the overseas Chinese (huaqiao) were portrayed as daring and successful entrepreneurs. They were heavily praised as genuine patriots, and their history was almost exclusively written in the light of their ties with the motherland. This was a means of promoting the idea that their fate was strongly connected with China and that, as a consequence, they should contribute to its economic growth through major investments. Since the beginning of the Xi Jinping era (2012), in tune with a more aggressive foreign policy (the Belt and Road Initiative), the huaqiao are seen as the bridgeheads of China’s outbound economic penetration.